2010
DOI: 10.3844/ajabssp.2010.77.83
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Development of Entrepreneurial Education in Iran’s Applied-Scientific Educational Centers for Agriculture

Abstract: Problem statement: An understanding of factors influencing entrepreneurial education in Iran's applied-scientific educational centers for agriculture is crucial for creating the new opportunities for students and encouraging them to involve in entrepreneurial activity. The purpose of this study was twofold. First, it determined the key factors that influence entrepreneurial education in Iran's appliedscientific educational centers for agriculture. Second, the study examined relationship of these factors with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
(5 reference statements)
0
5
1
Order By: Relevance
“…The possibility of creating new opportunities through agricultural entrepreneurship education is also mentioned in Azizi et al (2010). If education focuses on what this study identifies as significant barriers, targeted actions and learning practices can be proposed to reduce, if not eliminate these barriers, thus contributing to the success of this entrepreneurship model.…”
Section: Discussion and Research Agendamentioning
confidence: 97%
“…The possibility of creating new opportunities through agricultural entrepreneurship education is also mentioned in Azizi et al (2010). If education focuses on what this study identifies as significant barriers, targeted actions and learning practices can be proposed to reduce, if not eliminate these barriers, thus contributing to the success of this entrepreneurship model.…”
Section: Discussion and Research Agendamentioning
confidence: 97%
“…Initial evaluation reports and academic research have yielded baseline data that indicate that a large majority of teachers across subject areas considers handhelds to be effective tools in the classroom and believes that they can have a positive impact on student learning, especially because it is more realistic now than ever to attain a 1:1 computer to student ratio (Soloway et al, 2001;Vahey and Crawford, 2002;Van Hover et al, 2006;Champadaeng, 2010;Po-Klin et al, 2010;D'Silva et al, 2010 andAzizi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of an entrepreneurial education program are shaped by its characteristics, perspective as well as moderating factors for the participants (Valerio, Parton and Robb 2014). Azizi et al (2010) found economic, social, technical, managerial and regulatory factors to have influenced entrepreneurship education in Iran, while Alberta and Libecap (2000) reported that curriculum and related extra-curricular activities played an important role in the success of an entrepreneurship program. The effectiveness of youth entrepreneurship promotion programmes could largely be attributed to clear objective, commercial orientation, adequate funding, well-trained and properly supported staff, flexible and adaptable operation style, reliance on local business specialists, and collaboration with stakeholders as well as independent choice of enterprise activities by students (Chigunta 2002).…”
mentioning
confidence: 99%